P‐167: Efficiency Improvement of an Organic Light Emitting Display with Black Matrix for High Contrast Ratio. Issue 1 (May 2016) - Kuo, Ling Yi; Lee, Chun Yu; Chen, Yu Hung; Chen, Peng Yu; Lu, Hsueh Hsing; Lin, Yu Hsin; Wei, Mao Kuo; Lee, Jiun Haw; Lin, Hoang Yan
Abstract : In OLED displays, the black matrix (BM) layer is used to eliminate the unwanted ambient‐light reflection, but greatly decrease the brightness also. In this paper, the thickness of filler layer in the structure is designed to get more than 50% enhancement in efficiency.